Cognitive and mood side effects of lower urinary tract medication. Issue 10 (3rd October 2019) - Muderrisoglu, A. Elif; Becher, Klaus F.; Madersbacher, Stephan; Michel, Martin C.
ABSTRACT: Introduction : Muscarinic receptor antagonists, 5α-reductase inhibitors and α1 -adrenoceptor antagonists are frequently used drug classes for the treatment of lower urinary tract symptoms including those of overactive bladder syndrome and benign prostatic enlargement/benign prostatic obstruction. Areas covered : The authors review the evidence for adverse effects of these drug classes on cognitive function, mood and other functions of the central nervous system and discuss such effects against the evidence for mechanistic plausibility. Expert opinion : Muscarinic antagonists carry a risk for impaired cognition and other brain functions that differs quantitatively between compounds, being highest with oral formulations of oxybutynin. 5□-Reductase inhibitors can cause depressive symptoms even at low doses and starting several months after discontinuation of treatment. The evidence for α1 -adrenoceptor antagonists and specifically tamsulosin to cause dementia is controversial and lacks mechanistic plausibility. We recommend that physicians treating patients with lower urinary tract symptoms carefully monitor mental status prior to prescribing and periodically thereafter.